Archaeology of Conflict in Tanah Rejang: A Comparison of Indigenous and Colonial Defense Systems in Bengkulu in the 17th-19th Centuries - Benyamin Lufpi (GoAcademica Research & Publishing, 2026)
Bengkulu occupied a strategic position where local trading powers, the international pepper trade, and European colonial rivalries converged from the seventeenth century onward, giving rise to two distinct fortification traditions: the indigenous Rejang kutai—bamboo-fenced settlements (reduai) integrated with the community's social-cosmological structure, and the colonial fortifications of the British East India Company (EIC): Fort York, Fort Marlborough, Fort Anna, and Fort Linau. This paper builds a comparative interpretive framework for these two fortification typologies within a conflict archaeology lens, while mapping existing data gaps. As a conceptual study, it employs a qualitative approach based on secondary data synthesis, prior excavation reports, colonial archives, and ethnographic studies without primary fieldwork. Findings indicate that the two systems represent distinct epistemologies of conflict space: the Rejang kutai reflects an organic, community-scale defensive logic embedded in the landscape, while EIC forts reflect a geometric, centralized logic responding to larger geopolitical threats. The study also reveals significant disparities in the preservation of the three colonial forts, Marlborough well-maintained, Anna damaged as symbolic rejection, and Linau physically vanished and mythologized, analyzed through memory archaeology and critical heritage studies. The paper contributes to broadening the scope of Indonesian conflict archaeology, long dominated by colonial fortification studies, and proposes a primary field research agenda for the physical remains of Rejang kutai.